2017
DOI: 10.1371/journal.pone.0175514
|View full text |Cite
|
Sign up to set email alerts
|

M-COPA suppresses endolysosomal Kit-Akt oncogenic signalling through inhibiting the secretory pathway in neoplastic mast cells

Abstract: Gain-of-function mutations in Kit receptor tyrosine kinase result in the development of a variety of cancers, such as mast cell tumours, gastrointestinal stromal tumours (GISTs), acute myeloid leukemia, and melanomas. The drug imatinib, a selective inhibitor of Kit, is used for treatment of mutant Kit-positive cancers. However, mutations in the Kit kinase domain, which are frequently found in neoplastic mast cells, confer an imatinib resistance, and cancers expressing the mutants can proliferate in the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 57 publications
4
25
0
Order By: Relevance
“…In this study, blockade of the ER export of KIT with BFA/M-COPA decreased KIT’s autophosphorylation in leukemia cells. Together with the results previous reports [25, 27, 76, 77], our findings may offer a trafficking blockade of receptor mutants as a third strategy for inhibition of oncogenic signaling.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In this study, blockade of the ER export of KIT with BFA/M-COPA decreased KIT’s autophosphorylation in leukemia cells. Together with the results previous reports [25, 27, 76, 77], our findings may offer a trafficking blockade of receptor mutants as a third strategy for inhibition of oncogenic signaling.…”
Section: Discussionsupporting
confidence: 88%
“…Recently, we reported that in MCL, AL-mut, such as KIT D816V (human) and KIT D814Y (mouse), accumulates in EL (Table 1) [24, 25]. Unlike JM-mut, AL-mut in MCL activates AKT and STAT5 on EL and the ER, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, AMF-26 can induce complete tumor regression in breast cancer xenografts [54], reduce the proliferation of 39 different cancers in a variety of human organs (such as breast, colon, kidney, skin, central nervous system, lung, ovary, and stomach) [53,55], as well as diminish angiogenesis through suppressing the activation of the vascular endothelial growth factor receptor 1/2 (VEGFR1/2) and the nuclear factor-κB (NF-κB) pathways [56]. In addition, AMF-26 deactivates a mutant form of the endolysosomal Kit, leading to sensitizing carcinogenic mast cell to imatinib [57]. Finally, AMF-26 also prevents Shiga toxin-dependent apoptosis by decreasing its translocation into the Golgi apparatus [58].…”
Section: Arf1 and Its Inhibitors In Cancer Therapymentioning
confidence: 99%